2018
DOI: 10.1002/rcm.8093
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Athabasca lean oil sands and mixed surficial materials: Comparison of capillary electrophoresis/low‐resolution mass spectrometry and high‐resolution mass spectrometry

Abstract: Differences in measured amounts of total petroleum hydrocarbons by GC/FID and NAFCs by HRMS indicate that the two methods provide complementary information about the nature of dissolved organic species in a soil or water leachate samples. NAFC molecule class O S is a possible tracer for LOS seepage. CE/LRMS provides complementary information and is a feasible and practical option for source evaluation of NAFCs in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Amino acids and amines were used to characterize soil in the context of its hydration/dehydration properties . The characterization of naphthenic acids in overburden of oil sands with respect to its impact on environmental waters was performed by CE‐MS after conversion to naphthenic amines .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Amino acids and amines were used to characterize soil in the context of its hydration/dehydration properties . The characterization of naphthenic acids in overburden of oil sands with respect to its impact on environmental waters was performed by CE‐MS after conversion to naphthenic amines .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…On the other hand, only a few studies involving the analysis of NAs by CE can be found in the literature. These studies typically involve derivatization of NAs and analysis of PW by CE-MS [38,39]. More recently, a study on the NAs analysis using a microchip electrophoresis system has been reported [40].…”
Section: Introductionmentioning
confidence: 99%
“…The running electrolyte comprised 2% v/v formic acid with 30% v/v methanol. The same method was later used in 2018 by MacLennan et al to characterize oil sands using CE coupled with high and low-resolution MS and GC [39].…”
Section: Introductionmentioning
confidence: 99%
“…A number of publications have reported on the profiling of OSPW NAs and other AEOs with an aim of differentiating anthropogenic WSOs from naturally occurring bitumen-impacted groundwater WSOs. Techniques generally employ high resolution mass spectrometry techniques, including ultraperformance liquid chromatography time-of-flight (ToF) mass spectrometry, , multidimensional gas chromatography with ToF mass spectrometry, , liquid chromatography with Orbitrap mass spectrometry, high efficiency supercritical fluid chromatography with Orbitrap mass spectrometry, atmospheric pressure photoionization Fourier transform ion cyclotron resonance mass spectrometry, differential mobility mass spectrometry, and combinations of these technologies. , …”
Section: Introductionmentioning
confidence: 99%
“…Techniques generally employ high resolution mass spectrometry techniques, including ultraperformance liquid chromatography time-of-flight (ToF) mass spectrometry, 8,9 multidimensional gas chromatography with ToF mass spectrometry, 10,11 liquid chromatography with Orbitrap mass spectrometry, 12 high efficiency supercritical fluid chromatography with Orbitrap mass spectrometry, 13 atmospheric pressure photoionization Fourier transform ion cyclotron resonance mass spectrometry, 14 differential mobility mass spectrometry, 15 and combinations of these technologies. 16 The identification of OSPW source is complicated by the diverse and complex mixtures of organic compounds within all bitumen sources. These complexities are illustrated in differences in adamantane acids, diacids, 18 and AEO homologue profiles observed spatially within a pond, and between another pond sampled every 3 days over a 2 week period.…”
Section: ■ Introductionmentioning
confidence: 99%